Study on the effect of cutting parameters on bamboo surface quality using response surface methodology. (April 2021) - Liu, Yanhe; Zhou, Jianbo; Fu, Wansi; Zhang, Bin; Chang, Feihu; Jiang, Pengfei
Highlights: Feed speed showed a great influence on the Ra1 and Ra2. Spindle speed and cutting depth had little influence on the Ra1 and Ra2. Spindle speed, feed speed, and cutting depth had little effect on the Ra3. The best quality at medium spindle speed, low feed speed and low cutting depth. Abstract: The surface roughness of bamboo milling is one of the important indexes to evaluate the surface quality of bamboo milling. This article outlines the application of response surface methodology to optimize diamond cutting tools for bamboo cutting. In the experiment, different cutting speed, feed rate and depth of cut were used as cutting parameters, and the surface roughness was used to evaluate the surface quality of bamboo cutting. The results of the experiment were evaluated by variance analysis, graphical method and numerical method. The response surface method and expected value function are used to determine the mathematical model of bamboo surface roughness and the cutting parameter combination corresponding to the best cutting process. The result shows that the influence of feed speed on the surface roughness of the bamboo chord surface (Ra1) and the bamboo end surface roughness (Ra2) is more obvious, and the cutting parameters have little effect on the bamboo diameter surface roughness (Ra3). The cutting technology with the best surface quality is determined by optimization analysis. The established mathematical model can effectively predict the response within the range of cutting parameters, and the optimized combination of cutting parameters can obtain better surface quality of bamboo milling. The best bamboo surface roughness after optimization can be obtained at higher cutting speed, low feed speed and lower cutting depth is Ra1 = 1.5832 μm, Ra2 = 6.3626 μm, Ra3 = 2.2438 μm.